Queer inclusion in teacher education: Bridging theory, research, and practice - Murray, Olivia J. (Routledge, 2015)
Queer Inclusion in Teacher Education explores the challenges and promises of building queer inclusive pedagogy and curriculum into teacher education. Weaving together theory, research findings, and practical "how-to" strategies and materials, it fills an important gap by offering a clear roadmap and resources for influencing the knowledge, beliefs, and actions of faculty working with pre-service teachers. While the book has implications for policy change, most immediately, readers will feel empowered with ideas for faculty development they can implement in their own teacher education programs. Looking at both the politics and practices of teacher education and the ways in which queer issues manifest in schools, it is hopeful in suggesting that if teachers and pre-service teachers can critically reflect on homophobia and heteronormativity, they can begin to think about and relate to queer youth in a different, more positive and inclusive way. A Companion Website [http://queerinclusion.com] with additional activities and materials for teacher educators and faculty development and a practical guide enhances the usefulness of the book.
Keywords: LGBTQIA2+; approches et analyses; discipline; hétérosexisme; identités LGBTQIA2+; outils; ouvrages de références; pédagogie; pédagogie queer; queer; sciences de l'éducation; systèmes d'oppressions; systèmes éducatifs; thématiques

Deconstructing privilege: Teaching and learning as allies in the classroom - Case, Kim (Routledge, 2013)
Although scholarly examinations of privilege have increased in recent decades, an emphasis on privilege studies pedagogy remains lacking within institutions. This edited collection explores best practices for effective teaching and learning about various forms of systemic group privilege such as that based on race, gender, sexuality, religion, and class. Formatted in three easy-to-follow sections, Deconstructing Privilege charts the history of privilege studies and provides intersectional approaches to the topic. Drawing on a wealth of research and real-life accounts, this book gives educators both the theoretical foundations they need to address issues of privilege in the classroom and practical ways to forge new paths for critical dialogues in educational settings. Combining interdisciplinary contributions from leading experts in the field-- such as Tim Wise and Abby Ferber-- with pedagogical strategies and tips for teaching about privilege, Deconstructing Privilege is an essential book for any educator who wants to address what privilege really means in the classroom.
Keywords: amériques; approches et analyses; discipline; intersectionnalité; inégalités; justice sociale; outils; ouvrages de références; privilèges; régions géographiques; sciences de l'éducation; systèmes d'oppressions; états-unis